Trends, risk factors and mortality of unplanned 30-day readmission after heart transplantation. (14th October 2021) - Alvarez, P; Malik, A; Briasoulis, A
Abstract: Introduction: Outcomes after heart transplantation have improved, but the burden of readmissions is understudied. We sought to examine the incidence, risk factors, and associated mortality of unplanned 30-day readmissions following heart transplantation. Methods: This cohort study examined patient data from the United States population-based Nationwide Readmissions Database. All adults (age ≥18 years) who underwent isolated heart transplantation in US hospitals between January to November of 2012 to 2018 were included. The primary outcomes were 30-day readmission rates and readmission mortality. Results: A total of 14, 784 patients who underwent heart transplantation from 2012 to 2018 were included in our analysis. A total of 3299 (22.3%) patients were readmitted within 30 days after discharge. The median time from discharge to readmission was 9 days, and approximately 70% of the readmissions occurred within 15 days. After multivariable analysis, only CKD (Hazard ratio (HR): 1.11 95% CI 1.00–1.23) and length of stay (HR: 1.002; 95% CI 1.001–1.003; p<0.001) were associated with increased 30-day post-heart transplantation readmission. Readmissions diagnoses were heart transplantation complications, heart transplant rejection, postoperative infection, acute kidney injury, heart failure, pulmonary embolism, pneumonia, and pericardial effusion. The overall incidence of infection as a cause of readmission was 24.9%, with an associated mortality of 2.6% and a Median LOS of 7 days (4–14). The overall incidence of rejection was 38.0%, with a mortality of 1.2% and a median LOS of 5 days (3–8). Conclusion: Approximately 1 in 5 patients will be readmitted within 30 days after heart transplantation, and most of those readmissions will occur during the first two weeks after discharge. Readmissions were associated with a low mortality rate. FUNDunding Acknowledgement: Type of funding sources: None.